Evaluation of nitrate removal properties of magnetic anion‐exchange resins in water. Issue 5 (3rd June 2015) - Wang, Baijun; Song, Haiou; Wang, Changming; Shuang, Chendong; Li, Qiang; Li, Aimin
Abstract: BACKGROUND: High concentrations of nitrates in drinking water can lead to various types of cancers and to risks of contracting diseases. Two magnetic anion‐exchange resins (MD217 and MD218) were synthesized to remove nitrate quickly from aqueous solution. RESULTS: Results show that nitrate adsorption onto the resins fitted both pseudo‐first‐order and pseudo‐second‐order kinetic models. The equilibrium adsorption time for both resins was ∼10 min with the adsorption behaviour following the Freundlich adsorption isotherm model. MD218 showed high adsorption capacity and higher selectivity for nitrate in the presence of dissolved organic matter (DOM). MD217 showed higher selectivity in the presence of competing anions such as SO4 2 − in aqueous solution. Among the DOMs examined, humic acid affected nitrate removal the most, which can be explained well by a mechanism based on electrostatic interaction. CONCLUSIONS: Utilization of the resins in purification of water samples showed that both could be used for the treatment of ion‐containing polluted ground and surface waters. © 2015 Society of Chemical Industry